Prognostic model for the exemption of adjuvant chemotherapy in stage IIIC endometrial cancer patients - Yang, Xi-Lin; Yang, Feng-Leng; Kou, Ling-Na; Wu, Da-Jun; Xie, Cong (Frontiers in Endocrinology, 2022)
Background: To develop a nomogram to predict the survival for stage IIIC endometrial cancer (EC) patients with adjuvant radiotherapy (ART) alone and personalize recommendations for following adjuvant chemotherapy (ACT). Methods: 746 stage IIIC EC patients with ART alone were selected from the Surveillance, Epidemiology, and End Results (SEER) registry. Cox regression analysis was performed to identify independent risk factors. A nomogram was developed accordingly, and the area under the receiver operating characteristic curve (AUC) and C-index were implemented to assess the predictive power. Patients were divided into different risk stratas based on the total points deriving from the nomogram and survival probability was compared between each risk stratas and another SEER-based cohort of stage IIIC EC patients receiving ART+ACT (Cohort ART+ACT). Results: Five independent predictors were included in the model, which had favorable discriminative power both in the traing (C-index: 0.732; 95% CI: 0.704-0.760) and validation cohort (C-index: 0.731; 95% CI: 0.709-0.753). Patients were divided into three risk stratas (low-risk<135, 135≤middle-risk≤205 and high-risk>205), where low-risk patients had survival advantages over patients from Cohort ART+ACT (HR: 0.45, 95% CI: 0.33-0.61, P<0.001), however, the middle and high-risk patients were inferior to patients from Cohort ART+ACT in survival (P<0.001). Conclusion: A nomogram was developed to exclusively predict the survival for stage IIIC EC patients with ART alone, based on which the low-risk patients might be perfect candidates to omit the following ACT, however, middle and high-risk patients would benefit from the following ACT.